2017
DOI: 10.1016/j.jamda.2017.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Use of Medical Orders for Scope of Treatment for Heart Failure Patients During Postacute Care in Skilled Nursing Facilities

Abstract: Background Individuals with heart failure (HF) who are hospitalized and admitted to skilled nursing facilities (SNFs) are at high risk for rehospitalization and death. The care preferences of this high-risk population have not been studied. Objectives To describe care preferences of patients with HF admitted to SNFs for rehabilitation based on Medical Orders for Scope of Treatment (MOST) documentation, and evaluate goal-concordant care based on MOST documentation, emergency department (ED) visits, and hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…17 While most study designs were retrospective cohort studies, [11][12][13][14][16][17][18][19][20][21] Tolle's study was the only prospective study that collected data in real time and conducted chart reviews. 15 The combined study sample size was 5,688 individuals who documented EoL care wishes on POLST forms, recruited from a various care settings; nursing homes, 12,14,15,17 elderly care facilities, 16 community settings, 11,[18][19][20] and academic hospitals. 13 Majority of study samples were White (78.8%), female (54.3%), with mean age of 79.8 years.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…17 While most study designs were retrospective cohort studies, [11][12][13][14][16][17][18][19][20][21] Tolle's study was the only prospective study that collected data in real time and conducted chart reviews. 15 The combined study sample size was 5,688 individuals who documented EoL care wishes on POLST forms, recruited from a various care settings; nursing homes, 12,14,15,17 elderly care facilities, 16 community settings, 11,[18][19][20] and academic hospitals. 13 Majority of study samples were White (78.8%), female (54.3%), with mean age of 79.8 years.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…Specifically, 3 ("advance care planning"/exp OR "advance care planning") AND ("living will"/exp OR "living will") OR "care discussion" OR "end of life" OR "end of life care discussion" OR "care planning" OR "end of life care planning" OR "eol care planning" 175,307 2 "terminal care" OR "palliative therapy" OR "palliative nursing" OR "hospice nursing" OR "hospice" OR "end of life" 165,056 3 1AND2 40,075 4 "POLST" OR "MOLST" OR "COLST" OR "portable orders for life sustaining treatment" OR "physician orders for life sustaining treatment" OR "medical orders for life-sustaining treatment" OR "summary of physician orders for scope of treatment" OR "clinician orders for life sustaining treatment" OR "clinical orders for life sustaining treatment" OR "physician orders for scope of treatment" studies compared the preferred level of care (e.g., comfort only vs. limited vs. full treatment) indicated on POLST forms and whether wishes were respected. 13,16,17 Four studies examined the POLST wishes for hospitalization, 12,14,15,18 and 3 studies examined the POLST wishes for the receipt of care in an ICU setting. 15,16,18 Overall, preferred level of medical interventions showed concordance of 68.5% (range: 46%-91.1%), and the wishes to avoid/ transfer to hospital or ICU settings were concordant wish documented wishes 94% of the time (median 95.5%, range 85-100%).…”
Section: Concordance For Section B: Medical Interventionsmentioning
confidence: 99%
“…The use of POLST forms show promise, with recent evidence indicating that SNF residents with POLST forms in place receive goal-concordant care. 30,31 The recent interest in identifying causes of hospital readmissions from SNFs is not surprising, given the financial penalties hospitals pay and the new penalties SNFs will soon pay because of excessive patient readmissions. 6 Beyond financial consequences, hospital readmissions from SNFs are costly for the patient, often leading to in-hospital complications and high rates of patient mortality.…”
Section: Discussionmentioning
confidence: 99%
“…8 These findings highlight program and policy issues with POLST use in nursing homes and are consistent with a series of studies that have identified issues with nursing home use, including staff difficulty understanding and explaining the form, discomfort with issues raised by the form, and problems using the form to guide treatment. 4,9 One specific problematic practice that contributes to these difficulties is use of POLST as a universal code status order form to document CPR orders. In a recent National POLST survey of state POLST programs, almost half of program representatives who responded to the survey (15 of 33 or 45.4%) reported that POLST is at least sometimes used as a code status order form in their state and 9 (60%) of 15 who reported this occurs describe the practice as "very widespread" or "common" in their state (Vandenbroucke A.…”
Section: Paɵent Informaɵonmentioning
confidence: 99%